Costume Characteristics of Children Creation Dance in Kindergarten at Buleleng Bali - Sutrisno, Langen Bronto; Suartini, Luh; Budiarta, I Gusti Made (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2015)
Study related to characteristics of costumes worn in Children Creation Dance in kindergarten at Buleleng, Bali is aiming at (1) understanding the characteristics of children creation dance costume in kindergarten at Buleleng, Bali, (2) understanding the aesthetic characteristic of costume of children creation dance in kindergarten at Buleleng, Bali. The research employed qualitative method while the discussion part was presented in descriptive. Data was collected through observation, interview, literature, as well as documentation study. In a general view, characteristic of the costume was still in close proximity to the tradition but some others characteristics have quiet different to the tradition. Aesthetic aspect in dance costume that has adjacency to the tradition is shown in patterned costume, especially the use of kamen prada. The use of colour tends to be bright and cold which may show the atmosphere of happiness and assurance. On the other hand, the characteristics of costume is not traditional tends to emphasize dots and stripes. The impression of dots is shown in the use of sequin while the stripe impession is shown in fabric colour boundaries. In addition, the colours chosen for this type of costume are considerably similar to the colour chosen in traditional costume of creation dance which are bright and cold and give the impression of happiness and assurance.